UI/UX Design for Yamaha Arjawinangun Using the Double Diamond Method and Agile UX - Kartika, Geraldy Cornelius; Kusnadi, Kusnadi; Fahrudin, Rifqi (Jurnal Indonesia Sosial Sains, 2025)
This study aims to design and implement the UI/UX of a company profile website for Yamaha Agung Motor Arjawinangun using Framer. The main goal of the website is to facilitate access to company information and introduce the business to the broader public. This research applies the Double Diamond and Agile UX approaches to ensure that the needs of the customers and the general public are effectively met. The resulting website has been developed and is accessible online. Evaluation results show that users can easily understand and access the information provided on the site. This project marks an important step for Yamaha Agung Motor Arjawinangun in integrating technology into its business operations and establishing an online presence through a company profile website.